Injection-Locked Magnetron Using a Cross-Domain Analyzer - Fujii, Satoshi; Maitani, Masato M.; Suzuki, Eichi; Chonan, Satoshi; Fukui, Miho; Wada, Yuji (IEEE microwave and wireless components letters, 2016)
An injection-locked magnetron with an external oscillator was investigated to obtain the parameters of the equivalent circuit model. The magnetron was locked over the ratio of the input power to output power of -26 dB and had the resonance characteristics of a parallel LCR circuit model. Increasing the input power caused the anti-resonance frequency to become the original frequency of the magnetron; the range of the locking frequency was wider because of the lower Q value. The phase noise of the locked magnetron of -70 dBc at a 40-kHz offset was improved in comparison with an unlocked magnetron. The results show that an injection-locked magnetron with an external oscillator has great potential for obtaining a high power output.